Association between Drinking Habits and Oral Symptoms: A Cross-Sectional Study Based on Japanese National Statistical Data. (8th December 2020) - Kamoda, Takeshi; Komatsuzaki, Akira; Ono, Sachie; Tanaka, Satoshi; Yokoi, Yasuno
Abstract : Aim . The purpose of this study was to investigate the association between drinking habits and subjective symptoms of the oral cavity based on Japanese national statistical data. Methods . The subjects were 8, 698 respondents of the Japan National Livelihood Survey 2013, in their 30s to 60s. The association between drinking habits and each survey item was investigated by contingency table analysis and binary logistic regression analysis. Results . The proportion of people with drinking habits was 55.3% among men and 20.3% among women, and the proportion of men with drinking habits above the age of 40 years was high. Contingency table analysis indicated an association between drinking habits and the following items in men: subjective symptoms (p < 0.01 ), chewing difficulty (p < 0.05 ), subjective impression of health (p < 0.01 ), smoking habit (p < 0.01 ), and income level (p < 0.01 ). Analysis indicated an association between drinking habits and hospital visits (p < 0.01 ) and smoking habits (p < 0.01 ) in women. When comparing the response rates of symptoms and presence of disease stratified according to drinking habits, inflammatory and sensory system symptoms were common in those who had drinking habits, as were diabetes and gout. Binomial logistic regression analysis with drinking habit as the objective variable indicated statistically significant odds ratios for smoking habit (2.13; 95% CI: 1.65–2.75), difficulty in chewing (1.63; 95% CI: 1.01–2.62), and working hours (1.50; 95% CI: 1.10–2.04). This study identified a correlation between drinking habits and masticatory disorders, suggesting that the effects of drinking as a risk factor for dental diseases should be examined in greater detail in the future.